Proposal for a project management framework using Scrum and Kanban methodologies for digital product development - Sandim, Victor Bordim de Oliveira; Campanini, Luciano (Brazilian Journal of Production Engineering, 2024)
The research on agile project management aims to propose a project management framework using the agile methodologies SCRUM and Kanban for the development of digital products, based on the investigation, comparison, and combination of aspects and points of the two methodologies. Secondary objectives include defining the main purposes of a framework and its contribution to representing the structure of agile methodologies, understanding the key component groups that form SCRUM and Kanban, as well as identifying the main conceptual and practical differences between the two methodologies, in addition to consolidating performance metrics to support the analyses and results obtained. The research method used was a systematic review, which allowed for a generic model framework that prioritized a didactic, simple representation capable of aligning events, functions, artifacts, and rituals highlighted as the most significant within each methodology. Finally, it was possible to arrive at the proposition of a generic project management framework that combines fundamental elements and aspects of SCRUM and Kanban, from a model capable of aligning significant elements of each methodology, so that the work can contribute to the evolution of project management models.